Mountain ambush [large type] - White, Hope (White, Hope. Echo Mountain., 2017)
"A search-and-rescue mission turns deadly when Dr. Kyle Spencer is nearly killed by an assailant in the mountains. And when EMT Maddie McBride saves the doctor just in time, they're both targeted--but no one knows why. One thing's clear, though--from the moment Maddie finds Echo Mountain's most eligible bachelor left for dead, she can't stop thinking about him. But she's always been wary of the town's Dr. Dreamboat. And Spence's scarred heart's been shuttered since a childhood tragedy. As someone stalks the injured doctor's every move, though, Spence realizes that he needs the determined Maddie in his corner. However, he can't be sure their partnership will be enough to save them...especially against a seemingly all-knowing foe who's got them both in his deadly sights." -- Back cover.